Reflective thinking processes as a tool for social justice - Fumiatti, S.S. (International Journal of Pedagogy and Curriculum, 2025)
In the United States (US) kindergarten through twelfth-grade public school system, the classroom library has come to be a critical part of literacy instruction within the language arts classroom. This fact is especially true in the middle school grade levels (grades five through eight), where reading volume begins to rapidly increase. Additionally, a developmental norm for students within this age range includes a growing sense of independence and choice, as well as a desire to share and voice opinions. Classroom libraries have come to be tools that are used regularly and are heavily influential on the way that students grow to perceive themselves, the world around them, and the way they fit into that world. However, classroom libraries have remained stagnant and underrepresent the diverse populations of the students in those classrooms. This article aims to connect deep reflective thinking with anti-oppressive and transformative learning theories, exploring how these frameworks can be used to problematize current practices in classroom libraries. Through a content analysis of what is seen as deep and critical thinking practices and reflective thinking practices, anti-oppressive and transformative learning theories can be linked to foster a social justice classroom culture within US public middle school language arts classrooms. © 2025 Common Ground Research Networks. All rights reserved.
Keywords: Anti-oppressive Education; Classroom Libraries; Reflective Thinking; Social Justice; dept.edu; peer-reviewed

Facilitating interaction with police during routine traffic stops for persons with ASD - Grindle, H.; Sassu, K.A.; Dooley, J.M.; Farmer, E.B.; Volkmar, F.R. (Journal of Autism and Developmental Disorders, 2024)
A product of ASD socio-communicative-deficits and insufficient police training related to autism, ASD-police interactions have the potential to become problematic, with negative outcomes for ASD individuals and police alike. Thus, the combination of police acclimation, simulatory experience for drivers with ASD and the introduction of Connecticut’s recent Blue Envelope could improve overall experiences for drivers. A simulated routine traffic stop practice event, utilising pre- and post- measures was conducted in an effort to quantify drivers’ feelings about current and future interactions with police. Our prediction that participants would experience a statistically significant improvement in anxiety, comfort and self-perceived knowledge levels about future ASD-police interactions immediately following the intervention was confirmed. Our prediction that initially significant disparities between participants with and without police experience – those with previous police encounters versus those that don’t - would become not significant immediately following the intervention was disconfirmed. While the longitudinal data suggested that improved post-intervention ASD psychological measures remained statistically significant in the long-term, the sample responses to our long-term questionnaire were too few in number to make any definitive conclusions. It is suggested that practice traffic stops such as these could benefit both drivers with ASD and law enforcement nationwide. It is further suggested that police officer curriculums should include additional training regarding special populations. © The Author(s), under exclusive licence to Springer Science+Business Media, LLC, part of Springer Nature 2024.
Keywords: ASD; ASD-police Interaction; Blue Envelope Program; Driving; Pullover; Simulation; dept.edu; dept.sed; peer-reviewed

The effects of placement method on multilingual learner success in higher education - Key Jr, William (TESOL Journal, 2024)
In the United States, many actors are pushing for the use of grade point average (GPA) as the main placement tool for gatekeeper math and English courses for community college students (Quarles, 2022; Scott-Clayton, 2018; Turk, 2017). One community college system (pseudonymously, SXCC) in a New England state has begun placing students in initial math and English classes based on self-reported GPA. There have been studies on the effects of placement changes of this type (Belfield & Crosta, 2012; Hodara & Cox, 2016; Ngo & Kwon, 2014; Scott-Clayton, 2012). However, studies have not included the effects of these changes on multilingual learners (MLLs).Using a census of every MLL placed in SXCC in the summer and fall of 2020 and the spring of 2021 (N = 12,603), a MANOVA found that MLL students in the SXCC system who were placed using previous placement methods had a higher overall GPA than students placed using self-reported GPA (M = 3.32, SD = 0.740; M = 2.01, SD = 1.27, respectively) and had higher satisfactory academic progress (SAP) (M = 102.98, SD = 51.52; M = 57.66, SD = 55.53, respectively), and took longer to enroll in English 101 (M = 5.11, SD = 3.55; M = 2.36, SD = 1.76, respectively).
_eprint: https://onlinelibrary.wiley.com/doi/pdf/10.1002/tesj.835
Keywords: dept.edu; peer-reviewed

Take me to Nana's house - Mansfield, Christian (Independently published, 2023)
A young boy remembers fond childhood memories at his grandmother's house, where he learned the small things in life that truly mattered.
Keywords: SCSU-student; dept.edu

Connecticut Teachers' Perceptions and Evaluation of Their Competence to Teach English Language Learners in Elementary Classrooms. - Achhpal, Beena (2007)
Keywords: dept.edu; faculty_collection; sabbatical_report

Heeling Hearts and Soul Friends. - Duke, Suzanne (2005)
Keywords: dept.edu; faculty_collection; sabbatical_report

Integrating the Arts Across the Elementary School Curriculum - Gelineau, R. Phyllis (Wadsworth, 2012)
"This book is designed to assist pre-service and in-service classroom teachers in weaving music, visual arts, drama, and movement into the elementary school curriculum–thereby stimulating the learning process, enriching other subject areas, and providing opportunities for creative expression and self-fulfillment. Featuring content informed by the National Standards for the Arts, the book provides the basic tools and activities that teachers need to gain confidence in using the arts in their elementary classrooms. " – Publisher description.
Keywords: Arts; Curricula; Study and teaching (Elementary); Interdisciplinary approach in education; Education; Elementary; dept.edu; faculty_collection

Clustering Standards in Integrated Units - Ronis, Diane L. (Corwin Press, 2002)
Keywords: Education; Standards; United States; Interdisciplinary approach in education; Lesson planning; dept.edu; faculty_collection

Critical Thinking in Math - Ronis, Diane L. (Lesson Lab, 2002)
Keywords: Mathematics; Study and teaching; dept.edu; faculty_collection

Problem-Based Learning for Math and Science: Integrating Inquiry and the Internet - Ronis, Diane L. (SkyLight Professional Development, 2001)
Keywords: Mathematics; Study and teaching; Problem-based learning; Internet in education; Lesson planning; Study and teaching; Science; dept.edu; faculty_collection

Brain Compatible Assessments - Ronis, Diane L. (SkyLight, 2000)
Keywords: Educational tests and measurements; Learning; Psychology of; dept.edu; faculty_collection

Mathematical strategies and emergence of socially mediated metacognition within a multi-touch Dynamic Geometry Environment - Hegedus, S.J.; Otálora, Y. (Educational Studies in Mathematics, 2022)
Our research aimed to investigate the potential learning benefits to young children of implementing digital interactive multimodal technologies that provide both visual and haptic experiences in elementary mathematics classrooms. We studied the ways in which fourth-grade students collaboratively create collective strategies for solving mathematical problems utilizing dynamic geometry software with multi-touch interfaces, a combination we call a multi-touch Dynamic Geometry Environment. We examine in-depth two case studies each illustrating how mathematical strategies, collaboration, and socially mediated metacognition emerge in the small groups of children while working on an activity using the Geometer’s Sketchpad® on the iPad to make sense of an intuitive idea of covariation. We found that children’s interactions with their peers, the interviewer, and the mDGE favored the emergence of varied collaborative behaviors and socially mediated metacognitive processes that fostered the co-construction and development of mathematical strategies over a short period of time. © 2022, The Author(s), under exclusive licence to Springer Nature B.V.
1 citations (Crossref) [2023-10-31]
Keywords: Collaboration; Dynamic geometry software; Mathematical strategies; Multi-touch; Socially mediated metacognition; Young children; dept.edu; peer-reviewed

High school mathematics teachers’ discernment of invariant properties in a dynamic geometry environment - Nagar, G.G.; Hegedus, S.; Orrill, C.H. (Educational Studies in Mathematics, 2022)
Variance and invariance are two powerful mathematical ideas to support geometrical and spatial thinking, yet there is limited research about teachers’ knowledge of variance and invariance. In this paper, we examined how high school teachers deal with the task of looking for invariant properties in a dynamic geometry environment (DGE) setting. Specifically, we investigated if they even attend to invariant properties; what invariant properties they discern and discuss; and how DGE can support such discernment. Our analysis found that teachers tend to discern and discuss invariant properties mainly when they were probed to consider invariance. We also found four categories of invariant properties that seem to be important for a robust and rich understanding of geometric objects in the context of invariance and DGE. The use of DGE allowed teachers to see and interact with invariant properties, thus suggesting that accessing geometry dynamically may have structural affordances especially when exploring invariance. Teachers were able to enact different DGE movements to discern and discuss invariant properties, as well as to reason with and about them. We also saw that teachers’ backgrounds and past experiences can play an important role in their descriptions of invariant properties. Possible future research directions and implications to teacher education are discussed. © 2022, The Author(s), under exclusive licence to Springer Nature B.V.
4 citations (Crossref) [2023-10-31]
Keywords: Digital technologies; Discernment of invariant properties; Dynamic geometry environment; Geometric reasoning; Geometrical and spatial perception; Variance and invariance; dept.edu; peer-reviewed

Comparative perspectives on international school leadership: Policy, preparation, and practice - Magno, C.S. (Taylor and Francis, 2013)
Through a multi-country study, Comparative Perspectives on International School Leadership examines the current global spread of educational leadership, occurring rapidly and widely. Exploring five international case studies of leadership policy, preparation, and practice under the framework of policy borrowing and adaptation, Magno attempts to understand and account for commonalities and differences across country contexts. Rather than assuming a particular model or theory to leadership is best, Comparative Perspectives on International School Leadership takes a policy-oriented perspective and considers how and why certain approaches are being formulated and accepted, including an examination of motivations, influencers, actors, institutions, and implementation processes. Magno ultimately argues that efforts toward formalizing educational leadership reflect current global political objectives to improve schools by increasing accountability, transparency, and professionalism. This engaging book will be of interest to scholars and students in the fields of educational leadership and comparative education. © 2013 Taylor & Francis.
Journal Abbreviation: Comparative Perspectives on International School Leaderhip: Policy, Preparation, and Practice Pages: 247 Publication Title: Comparative Perspectives on International School Leaderhip: Policy, Preparation, and Practice
Keywords: dept.edu

Change theory: Towards a better understanding of software maintenance - Abdel-Raouf, A.; Hanafi, M. (WSEAS Transactions on Computers, 2014)
A successful Software maintenance process depends on three factors: the maintenance goals, the technical properties of the system and the people performing the software maintenance. Most of the current work to investigate software maintenance only considers the first two factors, ignoring the third factor, which limits the scope and accuracy of these approaches. In this paper, we use change theory to introduce a deeper understanding of the software maintenance process. We utilize three change theories: Lewin's, Prochaska and DiClemente's, and Lippit's theories to introduce three different software maintenance models. These models consider the three success factors and incorporate contextual information to help maintainers better understand the software maintenance task to bring about an effective change.
Keywords: Change stages; Change theory; Computer software maintenance; Computer software selection and evaluation; Contextual information; Software Quality; Software engineering; Software maintenance; Software maintenance process; Software properties; Software quality; Software-maintenance tasks; Success factors; Technical properties; dept.csc; ⛔ No DOI found

Assistive technology to provide access to the curriculum and increase independence - Dell, A.G.; Newton, D.A. (The SAGE Handb. of Special Education: Two Volume Set, Second Edition, 2014)
Journal Abbreviation: The SAGE Handb. of Special Education: Two Volume Set, Second Edition
Keywords: dept.edu

Foundations for the future: The potential of multimodal technologies for learning mathematics - Hegedus, S.J.; Tall, D.O. (Handbook of International Research in Mathematics Education: Third Edition, 2015)
Journal Abbreviation: Handb. of Int. Res. in Math. Educ.: Third Ed.
Keywords: dept.edu

Multiculturalism in four teacher education programs: for replication or transformation - Ensign, Jacque (Multicultural Perspectives, 2009)
9 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/027-152-287-216-696 tex.type: [object Object]
Keywords: dept.edu

Reimagining the school leadership paradigm in a postsocialist context - Magno, Cathryn (European Education, 2009)
7 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/132-074-900-255-294 tex.type: [object Object]
Keywords: dept.edu

It's all fun and games in Tiny's Diner: preschool programming in unusual exhibit spaces. - Moynihan, Nora; Diamant-Cohen, Betsy (Journal of Museum Education, 2012)
0 citations (Crossref) [2023-10-31] Citation Key Alias: pop00464 tex.type: [object Object]
Keywords: dept.edu

Adapting to the redesigned ap us history course - Santos, Brenda (Journal of the Gilded Age and Progressive Era, 2015)
0 citations (Crossref) [2023-10-31] tex.eissn: 1943-3557 tex.unique-id: ISI:000358527000008
Keywords: dept.edu

Proceedings of the third annual southern connecticut GeoGebra conference - Nabbout-Cheiban, Marie (2016)
Keywords: dept.edu; ⛔ No DOI found

Exploring how teacher-related factors relate to student achievement in learning advanced algebra in technology-enhanced classrooms. - Hegedus, Stephen; Tapper, John; Dalton, Sara (Journal of Mathematics Teacher Education, 2016)
In this study, we examine the relationship between contextual variables related to teachers and student performance in Advanced Algebra classrooms in the USA. The data were gathered from a cluster-randomized study on the effects of SimCalc MathWorlds®, a curricular and technological intervention as a replacement for Algebra 2 curriculum, on student learning of Algebra 2 content. Conditional measures (teacher background characteristics) and instructional measures (self-reported instructional preferences, stances, and classroom practices) were subjected to a variety of empirical analyses to discern their relationship to student learning. Researchers examined both the overall effect of teacher contextual variables on student learning and the specific effect of SimCalc on both teacher instructional measures and student performance. There is evidence to support that teachers who use the SimCalc curriculum value classroom communication, deep understanding of math concepts, and support for both routine and non-routine problems. © Springer Science+Business Media Dordrecht 2014.
6 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/037-412-463-374-521 tex.type: [object Object]
Keywords: Algebra; Connectivity; Dynamic representations; Student achievement; Teacher contextual variables; dept.edu

The impact of technology-enhanced curriculum on learning advanced algebra in US high school classrooms - Hegedus, Stephen J.; Dalton, Sara; Tapper, John R. (Educational Technology Research and Development, 2015)
We report on two large studies conducted in advanced algebra classrooms in the US, which evaluated the effect of replacing traditional algebra 2 curriculum with an integrated suite of dynamic interactive software, wireless networks and technology-enhanced curriculum on student learning. The first study was a cluster randomized trial and the second was a quasi-experimental replication study using a subset of the original treatment teachers. Both studies demonstrated significant impact on student learning of core algebra concepts including both procedural and conceptual problems. Various variables were modeled to understand the impact of such an intervention including demographic factors and class level. We found that being in an honors class significantly predicts learning gains but being in a non-honors SimCalc class significantly predicts learning gains versus all other groups. We also found significant effects of treatment on difference scores for problems which demanded simple procedural approaches and those that demanded complex conceptual understanding.
16 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/107-090-856-415-345 tex.eissn: [object Object] tex.unique-id: [object Object]
Keywords: Advanced algebra; Classroom connectivity; HLM; Randomized trial; SimCalc; Simulations; dept.edu

Exploring lake erie algae growth in an algebra class using geogebra - Nabbout-Cheiban, Marie (North American GeoGebra Journal, 2015)
Keywords: dept.edu; ⛔ No DOI found

Investigating why teachers reported continued use and sharing of an educational innovation after the research has ended - Hegedus, Stephen J.; Dalton, Sara; Roschelle, Jeremy; Penuel, William; Dickey-Kurdziolek, Margaret; Tatar, Deborah (Mathematical Thinking and Learning, 2014)
We investigated prospects for reported sustainable adoption and sharing of an educational innovation through survey research including online questionnaires and telephone interviews. This investigation is part of the Scaling-Up SimCalc experimental program, which combines dynamic representational algebra software (SimCalc MathWorlds) with integrated curriculum and small professional development workshops focused on how to use the software and how to integrate this intervention into the larger year-long curriculum. Teachers who (1) perceived the usefulness of the SimCalc professional development as being consistent with personal aims and (2) perceived specific affordances of the software/curriculum to be valuable were more likely to report continued use of the innovation after the research had ended and that they had shared it with colleagues over time.
2 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/054-625-976-984-638 tex.eissn: [object Object] tex.orcid-numbers: [object Object] tex.unique-id: [object Object]
Keywords: dept.edu

SimCalc: democratizing access to advanced mathematics - Tatar, Deborah; Roschelle, Jeremy; Hegedus, Stephen (International Journal of Designs for Learning, 2014)
2 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/007-705-510-298-236
Keywords: dept.edu

Using technology to prompt good questions about distributions in statistics - Nabbout-Cheiban, Marie; Fisher, Forest; Edwards, Michael Todd (The Mathematics Teacher, 2017)
Revisions of a textbook problem enhance the underlying tasks and foster conceptual understanding.
0 citations (Crossref) [2023-10-31]
Keywords: dept.edu; peer-reviewed

Intuitive thinking and misconceptions of independent events: a case study of us and french pre-service teachers - Nabbout-Cheiban, Marie (International Journal of Research in Undergraduate Mathematics Education, 2016)
In this article we study the conceptions of an American and a French group of undergraduate pre-service teachers regarding the concept of independent events. Specifically, we study the role that intuition plays in their answers, ascertain the presence of probabilistic biases, and compare the findings with previous results collected on a different population. Participants were asked to provide essay-type answers to a three-part questionnaire that asked them to solve problems, react to hypothetical students’ answers, and answer direct questions. The concept of independent events was problematic for most participants as was the distinction between mutually exclusive and independent events. In addition, representativeness bias and the Falk Phenomenon were observed among several participants.
5 citations (Crossref) [2023-10-31]
Keywords: dept.edu

Uses of technology in upper secondary mathematics education - Hegedus, Stephen; Laborde, Colette; Brady, Corey; Dalton, Sara; Siller, Hans-Stefan; Tabach, Michal; Trgalova, Jana; Moreno-Armella, Luis (Springer, 2017)
Citation Key Alias: lens.org/123-483-507-127-369
Keywords: dept.edu

Topic Study Group No. 43: Uses of Technology in Upper Secondary Education (Age 14–19) - Hegedus, Stephen; Laborde, Colette; Moreno Armella, Luis; Siller, Hans-Stefan; Tabach, Michal (Proceedings of the 13th International Congress on Mathematical Education, 2017)
0 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/080-144-411-088-356, pop00176
Keywords: dept.edu